UPAYA MENINGKATKAN KEDISIPLINAN PESERTA DIDIK MELALUI KEGIATAN TADARUSAN SEBELUM MEMULAI PEMBELAJARAN KELAS VIII DI MTSN 11 AGAM - Sarah Salsabilla; Isnando Tamrin; Roswita (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research was conducted at MTsN 11 Agam, specifically in Koto Kaciak, Tanjung Raya District, Agam Regency, West Sumatra using a qualitative approach. Power collection techniques are carried out through observation and interviews. The aim of this research is to improve student discipline through tadarusan efforts before starting learning, especially class 11 MTsN 11 Agam. The results of the research are: (1) students' discipline is considered very good, it is indicated that students show polite attitudes towards parents, teachers, colleagues and other people, both those of the same religion and those of different religions. (2) the benefits of Al-Quran tadarus activities before starting learning so that students have good religious abilities and insight and increase discipline in studying religion, (3) things that become obstacles in Al-Quran tadarus activities include minimal student interest, lack of enthusiastic, other factors, parents, environment, educators, and (4) Teacher solutions in overcoming obstacles to Al-Quran tadarus activities including increasing support from school management, increasing communication and cooperation from parents, completing facilities.